2022
DOI: 10.3390/genes13050823
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite and Gene Expression Analysis Underlying Temporal and Spatial Accumulation of Pentacyclic Triterpenoids in Jujube

Abstract: Jujube (Ziziphus jujuba Mill.) has attracted increasing attention because of its fruits’ high nutritional and medicinal value, which produce pentacyclic triterpenoids with valuable pharmacological activities beneficial to human health. However, the dynamic accumulation and metabolism pathway of triterpenoids remain unknown in jujube. Here, we performed metabolite assays of triterpenoids and expression analysis of genes involved in the corresponding metabolic processes on cultivated jujube (Z. jujuba cv. Junzao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Triterpenoids were extracted following Wen et al [ 5 ], using 0.5 mg freeze-dried samples. For triterpenoid content analysis, the extracted material was dissolved in 5 mL 90% MeOH and was analyzed using high-performance liquid chromatography (HPLC), following the method of Wen et al [ 5 ]. The triterpenoid standards were obtained from Sigma-Aldrich and were used for identification and quantification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triterpenoids were extracted following Wen et al [ 5 ], using 0.5 mg freeze-dried samples. For triterpenoid content analysis, the extracted material was dissolved in 5 mL 90% MeOH and was analyzed using high-performance liquid chromatography (HPLC), following the method of Wen et al [ 5 ]. The triterpenoid standards were obtained from Sigma-Aldrich and were used for identification and quantification.…”
Section: Methodsmentioning
confidence: 99%
“…Most identified terpenoids are synthesized by plants and are induced by hormones such as methyl jasmonate (MeJA) and salicylic acid (SA) [ 3 , 4 ]. MeJA treatment can promote the accumulation of triterpenoids [ 5 ]. Triterpenoids play important roles in plant respiration, photosynthesis, growth and development, and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the structural genes ZjHMGR, ZjFPS, ZjSQS, ZjOSC, and ZjCYP450 might be involved in triterpenoid synthesis. 10 Correlation analysis showed that the expression of ZjFPS and ZjSQS were highly correlated with the content of triterpenoids. The expression levels of ZjFPS and ZjSQS were higher in the buds and young leaves than in other tissues in jujube.…”
Section: Patterns Of Triterpenoid Metabolites Accumulation In Jujubementioning
confidence: 99%
“…Next, 500 μL of perchloric acid and 2.25 mL of glacial acetic acid were added to the reaction mixtures. The extraction and quantification of pentacyclic triterpenoids via HPLC were performed following the procedure of Wen et al 10 The petroleum ether extract of jujube fruit was analyzed by GC-MS following the method described in Reddy et al 35 with slight changes. Three biological replicates and three technical replicates were performed in all experiments.…”
Section: Measurement Of Total Triterpenoids High-performancementioning
confidence: 99%
See 1 more Smart Citation